The pottery and graffiti from the vicus of Ockenburgh, The Hague (NL) - van der Linden, Ester (Rei Cretariae Romanae Fautorum Acta, 2017)
In the dunes of Ockenburgh, in the city of The Hague (province of Zuid-Holland, the Netherlands), a small military fort and a much larger vicus were located. The site of Ockenburgh is situated south of the end part of the Lower Rhine limes with its auxiliary forts, and in the vicinity of the municipium Forum Hadriani. Nowadays the site is located near the North Sea, but in the Roman period the coastline ran west of the present coastline, hence the site was situated further inland.